Quality Indicators for Reviews of Research in Special Education. Issue 4 (2nd October 2018) - Talbott, Elizabeth; Maggin, Daniel M.; Van Acker, Eryn Y.; Kumm, Skip
ABSTRACT: Reviews of research in special education have a unique place in the scientific literature, with the potential to inform a broad audience about the effectiveness and acceptability of assessment and intervention strategies for a heterogeneous group of children and youth. Results from reviews are useful to school leaders, practitioners, parents, policymakers, grant funders, researchers, journal editors, and reviewers. Despite an international movement toward the implementation of evidence-based practices, which includes quality indicators for reviews of research, the field of special education has not yet embraced its own set of review indicators. In this manuscript, we make the case for and propose a set of quality indicators for special education, with the goal of making all reviews in the field trustworthy, transparent, and systematic. Attaining a high level of quality in research reviews will then help researchers guide consumers to select the most effective interventions for youth with disabilities.